Pharmacotherapy of Ischemia-Reperfusion Injury of Transplanted Kidneys in Children: Comparative Study - Victor A. Goryainov; Michael M. Kaabak; Nadezhda N. Babenko; Margarita M. Morozova; Aleksandr G. Aganesov; Elena N. Platova; Olga V. Dymova; Vasiliy V. Panin; Aleksey K. Gramotnev (Union of pediatricians of Russia, 2017)
Background. Prevention of ischemia-reperfusion injury of the allograft (IRIA) is an urgent problem in transplantology, which largely determines the prognosis for both the transplanted organ and the patient as a whole.Objective. Our aim was to study the effectiveness of eculizumab in comparison with plasmapheresis during induction  immunosuppressive therapy in kidney transplantation in children.Methods. The retrospective study includes children with terminal phase of chronic renal failure who have received kidney transplants from either a living relative or deceased donor. The age of patients is from 1 year to 18 years. Induction immunosuppression in both groups was performed with alemtuzumab. Group 1 (main) included children who were treated with eculizumab to prevent IRIA, Group 2 (comparison) included children who were treated with plasmapheresis for the same purpose. The comparative analysis was carried out according to the following criteria: the rate of blood creatinine subnormalization (in days), the rate of glomerular filtration (in ml/min) 30 days after the operation; daily protein excretion (mg/24 h) 30 days after organ transplantation; morphological characteristics of renal biopsy samples by Banff 30 days after surgery.Results. During the comparative analysis from December 2012 to November 2016, eculizumab was administered to 32 patients, 24 patients underwent plasmapheresis. In Group 1, blood creatinine normalized almost 4 days earlier than in Group 2 (p=0.0049); the glomerular filtration rate in Group 1 was 4.5 times higher than in Group 2 (p=0.0018). Daily proteinuria in Group 1 was 4 times lower than in Group 2 (p=0.0019).Conclusion. The carried out study showed better indices of renal allograft function when using eculizumab in comparison with plasmapheresis: consequently, eculizumab more effectively suppresses IRIA than plasmapheresis.